Pattern recognition and machine intelligence : 6th International Conference, PReMI 2015, Warsaw, Poland, June 30-July 3, 2015, Proceedings /: 6th International Conference, PReMI 2015, Warsaw, Poland, June 30-July 3, 2015, Proceedings. (2015) - Unknown
No abstract available